Wandering spleen in a geriatric patient – a rare presentation of gastric volvulus. Issue 6 (May 2019) - Gandhi, Christy; Fowler, Rachel L; Hersey, Sean; Heffernan, Daithi S; Stafford, Todd
We report atypical gastric outlet obstruction in a geriatric patient caused by acute mesenteroaxial gastric volvulus precipitated by a wandering spleen.